Low Serum 25- Hydroxyvitamin D among Beta-Thalassemia Patients in Iraq - Riham Hussein Noor Almosawi (Journal of Global Pharma Technology, 2018)
This study aimed to investigate characteristics of patients like type of Beta-Thalassemia, age, gender, and estimation of vitamin D level in the serum of patients with β – thalassemia. Samples of blood were collected from 98 β-thalassemia patients and 32 healthy controls. The quantitative assays of 25-hydroxy vitamin D were detected by using the quantitative sandwich ELISA technique. Serological experimental analysis found that the mean 25-hydroxy vitamin D was significant decrease in patients group in comparison to control subjects (P<0.001).Keywords: β-thalassemia, Patients, Serum, 25-Hydroxyvitamin, Iraq.